Generation Impact - Goldseker, Sharna; Moody, Michael (Ascent Audio, 2019)
An insider's guide to the coming philanthropic revolution Meet the next generation of big donors-the Gen X and Millennial philanthropists who will be the most significant donors ever and will shape our world in profound ways. Hear them describe their ambitious plans to revolutionize giving so it achieves greater impact. And learn how to help them succeed in a world that needs smart, effective donors now more than ever. As "next gen donors" step into their philanthropic roles, they have not only unprecedented financial resources, but also big ideas for how to wield their financial power. They want to disrupt the traditional world of charitable giving, and they want to do so now, not after they retire to a life of philanthropic leisure. Generation Impact pulls back the curtain on these rising leaders and their "Impact Revolution," offering both extensive firsthand accounts and expert analysis of the hands-on, boundary-pushing, unconventional strategies next gen donors are beginning to pursue.